Perceptions of a Strategy to Prevent and Relieve Care Provider Distress in the Neonatal Intensive Care Unit - Okah, Felix A.; Wolff, Dawn M.; Boos, Virginia D.; Haney, Barbara M.; Oshodi, Adebayo A. (American Journal of Perinatology, 2012)
Background A Midwestern neonatal intensive care unit (NICU) employs a multidisciplinary conference, the Comprehensive Care Round (CCR), to facilitate communication and consensus building and thereby prevent or address moral distress within the health care team.Methods A cross-sectional survey, 3 years after implementation of CCR, to evaluate health care providers' (HCP) perceptions of comfort with expressing distress, support from team members in care situations that evoke moral distress, barriers to communication, and attainment of CCR objectives.Results Of 370 HCP, 116 (31%) participated in the survey (42% nurses, 37% allied health, and 21% medical); 51% had previously attended CCR. CCR attendance was higher among HCP aged >35 years, those who cared for CCR patients, and nonnurses. Neonatologist were more likely than others (44% versus 4%, p <0.01) to report that referred cases were not overdue for discussion and that families appreciated the attention their child received from CCR. Of note, HCP who were comfortable with expressing distress also felt supported by team members (R = 0.5, p <0.001).Conclusion CCR, developed to prevent or address moral distress, occurs later than most NICU HCP consider appropriate and appears to better serve HCP who are already comfortable with discussing moral distress. Helping HCP become comfortable with crucial conversations should support meaningful participation and contribution to multidisciplinary conferences.
Keywords: moral distress; NICU; communication; multidisciplinary